Silence of the Wolf - Spear, Terry (Naperville, IL : Sourcebooks Casablanca, 2014)
Gray werewolf Tom Silver searches the Rockies for the wolves responsible for killing local livestock, but soon must rescue an imprisoned female werewolf/coyote shifter mix from a plane crash and hide her from her captors.
Keywords: Werewolves -- Fiction; Shapeshifting -- Fiction; Blizzards -- Fiction; Interpersonal attraction -- Fiction; Colorado -- Fiction; Rocky Mountains -- Fiction; Paranormal fiction; Romance fiction